Host range of rugose spiraling whitefly, (Aleurodicus rugioperculatus) martin and its incidence and damage on coconut plant in coastal region of Bangladesh: Host range of rugose spiraling whitefly on coconut (SAARC Journal of Agriculture, 2022)
Rugose spiraling whitefly, Aleurodicus rugioperculatus Martin (Hemiptera: Aleyrodidae) is an invasive pest causing severe damage to several plant species. Surveys were conducted in the farmers’ orchards of 11 coastal districts of Bangladesh namely Patuakhali, Barguna, Barishal, Khulna, Bagherhat, Pirojpur, Jhalokathi, Bhola, Laxmipur, Noakhali and Cox’s Bazar to know the host range of rugose spiraling whitefly and its incidence and damage in coconut during July 2021 to June 2022. Results revealed that a total of 22 plant species from 16 families were recorded as hosts of A. rugioperculatus. Among the host plants 4 hosts were infested by A. rugioperculatus in which all the life stages such as egg spirals, nymphs and adults of whitefly were noticed whereas in other 18 host plants only the egg stages were observed. The highest incidence of whitefly egg spirals, nymphs and adults per leaflet of coconut was observed in September 2021 at Bagherhat followed by October, November and May 2022 while the lowest was in July 2021 at Cox’s Bazar followed by June, January, February 2022 and December 2021. The highest percent (97%) infested tree was recorded in Bagherhat district while the lowest percent infested tree (68%) was in Cox’s Bazar. The highest percent (96.23%) of infested fronds per tree were recorded in Bagherhat district and the lowest percent infested fronds per tree (67.23%) was in Cox’s Bazar. The highest percent (84%) of leaflet area occupied by this insect was recorded in Bagherhat and the lowest percent was in Cox’s Bazar (48%).SAARC J. Agric., 20(2): 183-197 (2022)